2003
DOI: 10.1016/s1044-0305(03)00542-7
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase dissociation pathways of multiply charged peptide clusters

Abstract: Numerous studies of cluster formation and dissociation have been conducted to determine properties of matter in the transition from the condensed phase to the gas phase using materials as diverse as atomic nuclei, noble gasses, metal clusters, and amino acids. Here, electrospray ionization is used to extend the study of cluster dissociation to peptides including leucine enkephalin with 7-19 monomer units and 2-5 protons, and somatostatin with 5 monomer units and 4 protons under conditions where its intramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Dissociation of such complexes in the gas phase usually proceeds via the so-called asymmetric charge partitioning, where a single polypeptide chain is ejected from a metastable complex and carries a disproportionately high number of charges [13]. An example of such a process is presented in Figure 2, where mild collisional activation of large protein complexes (14-meric molecular chaperon GroEL) in the ESI interface results in ejection of a highly charged monomeric ion from the complex.…”
Section: Can Charge State Distributions Be Used To Provide Meaningfulmentioning
confidence: 99%
“…Dissociation of such complexes in the gas phase usually proceeds via the so-called asymmetric charge partitioning, where a single polypeptide chain is ejected from a metastable complex and carries a disproportionately high number of charges [13]. An example of such a process is presented in Figure 2, where mild collisional activation of large protein complexes (14-meric molecular chaperon GroEL) in the ESI interface results in ejection of a highly charged monomeric ion from the complex.…”
Section: Can Charge State Distributions Be Used To Provide Meaningfulmentioning
confidence: 99%
“…In a double resonance experiment [77,78], a frequency corresponding to the cyclotron resonance frequency of an ion suspected to be an intermediate in a consecutive dissociation process is continuously irradiated over the course of a dissociation experiment. The disappearance of lower mass ions confirms that the irradiated ion is an intermediary in the formation of those ions.…”
Section: Double Resonance Experimentsmentioning
confidence: 99%
“…It has also been demonstrated that the degree of asymmetric charge partitioning for protein homodimers depends on the conformational flexibility of the proteins in the complex, the charge state of the complex, the internal energy deposition, and the composition of the electrospray solutions from which the complexes are formed [56]. For larger clusters consisting of identical subunits, fission was observed to occur with preferential formation of protonated dimers, and with increasing charge state and cluster size, increasing formation of protonated monomer was observed [57]. The extent of fission versus neutral loss for these clusters could be related to that observed for multiply charged metal clusters with one important difference: Differences in conformational flexibility of the monomer sub-units within a cluster results in differences in the branching ratios of the various dissociation processes observed for these multiply protonated biomolecule clusters [57].…”
mentioning
confidence: 98%